Two-year outcomes of bioresorbable vascular scaffold versus drug-eluting stents in coronary artery disease: a meta-analysis. Issue 14 (23rd January 2017) - Nairooz, Ramez; Saad, Marwan; Sardar, Partha; Aronow, Wilbert S
Abstract : Background: Data regarding long-term clinical outcomes with everolimus-eluting bioresorbable vascular scaffold (BVS) versus second-generation drug-eluting stents (DES) are scarce. Methods: We searched online databases until October 2016 for studies comparing BVS versus DES reporting outcomes at 2 years of follow-up. We performed a meta-analysis comparing BVS with DES across the spectrum of coronary artery disease (CAD). Random effects model OR was calculated for outcomes of interest including device-oriented composite events (DOCE; defined as composite of cardiac mortality, target vessel myocardial infarction (TV-MI), and ischaemia-driven target lesion revascularisation (TLR)), all-cause mortality, definite stent thrombosis, TV-MI and TLR. Results: A total of 2360 patients enrolled in five studies met criteria for inclusion in this analysis. At 2 years, BVS was associated with higher rates of DOCE (6.9% vs 4.5%, OR=1.53; 95% CI 1.06 to 2.23; p=0.02), absolute risk increase (ARI) 2.4%, relative risk increase (RRI) 53%, TV-MI (4% vs 1.8%, OR=1.94; 95% CI 1.02 to 3.67; p=0.04), ARI 2.2%, RRI 122% and definite stent thrombosis (2.1% vs 0.6%, OR=3.39; 95% CI 1.46 to 7.88; p=0.005), ARI 1.5%, RRI 250% compared with DES. No differences in all-cause mortality (OR=0.86; 95% CI 0.26 to 2.81; p=0.80) and TLR (OR=1.44; 95% CI 0.81 to 2.54; p=0.21) were observed between both groups. Conclusions: BVS may be associated with worse long-term clinical outcomes compared with DES. Randomised clinical trials are encouraged to expeditiously report long-term safety and efficacy outcomes and identify predictors of adverse events with BVS compared with DES.